AESTHETIC AND STRENGTHS CHANGES IN THERMALLY TRETAED BEECH FALSE HEARTWOOD (Fagus Sylvatica L.) - Mihajlovski Nikola; Konstantin Bahchevandjiev (Faculty of Design and Technologies of Furniture and Interior-Skopje, 2013)
This paper discuses the aesthetic changes and some of the mechanical changes in native beech wood (Fagus sylvatica L.) and beach wood which has developed false heartwood, before and after being thermally treated. The aesthetic properties, colour and texture are determined visually, whereas some of the mechanical properties which have been tested are pressure strength, bending strength and the elasticity modulus under stress (when bending wood). Discolouration, also called false heartwood, becomes identical with the colour of native beech after being treated at 1800C, and at 2300C the colour and texture get dark. Pressure strength of native beech wood increases after thermal treatment, but it is lower than in beech false heartwood. After thermal treatment there are no significant differences in bending strength and elasticity modulus of native beech wood and beech false heartwood. Thermal treatment at 1800C drastically reduces the bending strength, but increases the elasticity modulus.
Keywords: beech wood, false heartwood, thermal treatment, color, texture, pressure strength, bending strength, elasticity modulus